Challenges in the transition from adolescence to adulthood in autistic people: A bibliographical analysis (Research, Society and Development, 2024)
This article addresses the challenges faced by autistic individuals in the transition from adolescence to adulthood, focusing on the psychosocial, educational, and professional difficulties that arise during this critical period of development. The transition to adulthood is a complex process that involves adaptations in several spheres of life, such as education, work, independence, and social relationships. The objective of this study is to conduct a literature review on the challenges of the transition from adolescence to adulthood in autistic individuals. The research is bibliographic in nature, bringing together studies and scientific publications on the subject to analyze the barriers encountered by autistic individuals during this phase and the most effective support strategies. The literature review indicates that the lack of adequate preparation for adulthood, associated with the scarcity of specialized resources and limited understanding of the needs of autistic individuals, results in a high rate of inactivity, unemployment, and difficulties in socialization for this group. The article highlights the importance of public policies and inclusion programs that favor a more structured and effective transition, enabling a more autonomous adult life that is integrated into society.